HLA and Mooren's ulceration. Issue 1 (1st January 2000) - Taylor, Craig J; Smith, Sheila I; Morgan, Catherine H; Stephenson, Susan F; Key, Tim; Srinivasan, M; Cunningham, Emmett; Watson, Peter G
Abstract : BACKGROUND: Mooren's ulcer is a progressive intractable destructive peripheral ulceration of the cornea, probably of autoimmune aetiology. The disease is rare in the northern hemisphere but is more common in southern and central Africa and the Indian subcontinent. Although rare, its predominance in certain racial groups and their second generation migrants worldwide indicates a genetic as well as a geographic predisposition. The highly polymorphic human leucocyte antigens (HLA) confer genetic susceptibility to several autoimmune disorders. Therefore, a possible link between Mooren's ulcer and HLA type was investigated. METHODS: Patients (n=22) with non-infective destructive peripheral corneal inflammatory disease were recruited worldwide. Differential diagnosis confirmed Mooren's ulceration in 12 cases. HLA typing (HLA-A, B, C, DRB, DQB) was performed by serology and PCR using sequence specific primers. The patients came from varied ethnic backgrounds and their HLA typing results were compared with published data from ethnically matched control populations. RESULTS: Of the 12 patients with Mooren's ulcer, 10 (83%) were HLA-DR17(3) positive (including all nine patients of Asian, Indonesian, and black African origin), and 10 (83%) were HLA-DQ2 positive. The frequency of HLA-DR17(3) and DQ2 was higher in the Mooren's ulcer group compared to published data from ethnically matched control populations, where the expected antigen frequencies range between 5% and 40%. CONCLUSION: These results suggest a possible association between HLA-DR17(3) and/or DQ2 and susceptibility to Mooren's ulcer.